UROGENITAL TRACT MICROFLORA IN SEXUAL PARTNERS WITH CHRONIC GENITOURINARY TRICHOMONIASIS - N. A. Neronova; E. V. Simonova; E. A. Zhigalova; Yu. M. Bardaeva (Acta Biomedica Scientifica)
Trichomonas infection is a scientific and clinical problem in dermatology, urology, obstetrics and gynecology. This infection in men and women is often causes to urethritis, cystitis, prostatitis, post-abortion infection, premature labor and other diseases. This literature review has shown that in spite of a lot of numbers of scientific data concerning the impact of trichomoniasis to urogenital bioceonosis of both men and women, there is no enough data about influence of trichomoniasis to urinary microecology in sexual partners. Meanwhile, this question is in the field of scientific and applied interest and need to be studied.